Exploring Pregnant Women’s Experiences in Recognizing the Signs and Symptoms of Preeclampsia: A Qualitative Study - Rina Inda Sari; Sri Wahyuni (PT. Nasyah Medika Care, 2026)
Background: Preeclampsia remains a major cause of maternal and perinatal morbidity and mortality. Early detection depends not only on clinical screening but also on pregnant women’s ability to recognise and interpret warning signs. However, symptoms may be normalised as ordinary pregnancy discomforts, potentially delaying timely care. Research Objective: This study explored pregnant women’s experiences of recognising, interpreting, and responding to the signs and symptoms of preeclampsia. Methods: A descriptive phenomenological study was conducted in the working area of Katobengke Community Health Centre, Baubau, Indonesia, from April to June 2025. Twenty pregnant women were recruited through criterion-based purposive sampling. Data were collected through individual, in-depth semi-structured interviews, supported by field notes and observations. Colaizzi’s method guided the analysis. Credibility was supported through member checking, peer debriefing, triangulation, reflexivity, and an audit trail. Results: Four themes were identified: interpreting ambiguous bodily changes, constructing knowledge about preeclampsia, negotiating decisions within the family, and moving from uncertainty to professional care. Participants frequently considered headaches, swelling, and visual disturbances normal pregnancy experiences until the symptoms persisted or worsened. Fragmented health information, family interpretations, access barriers, and healthcare professionals’ responses shaped care-seeking decisions. Data saturation was achieved when later interviews produced no new thematic insights. Conclusion: Recognition of preeclampsia is a socially situated interpretive process rather than simple factual knowledge. Antenatal services should provide repeated, understandable, action-oriented education, involve influential family members, and ensure responsive referral pathways while maintaining routine clinical screening.